499 CLINICAL AND IMAGING FEATURES OF A CASE OF HEMORRHAGIC CHOLECYSTITIS WITH PERFORATION. (10th December 2015) - Helmy, M.; Yedavalli, R. V.; Cohen, A. J.
Abstract : Background: Hemorrhagic cholecystitis is a rare complication of acute cholecystitis that carries a high mortality rate and may be clinically indistinguishable from uncomplicated cases. Accurate recognition is necessary to allow for prompt, appropriate intervention and avoid gallbladder perforation. Though not traditionally utilized in evaluation of acute gallbladder disease, CT serves as a valuable adjunct to sonography and scintigraphy in evaluation of gallbladder pathology. Methods: We review the clinical and imaging features of a case of acute cholecystitis complicated by hemorrhage and perforation. A 37 year-old male with hepatitis C and alcoholic cirrhosis presented to the ED with a one-week history of right upper quadrant abdominal pain, nausea, vomiting, and fever. Laboratory evaluation was significant for thrombocytopenia and elevated liver and pancreatic enzymes. An abdominal sonogram demonstrated findings consistent with acute calculous cholecystitis. The patient underwent ERCP and was managed medically with intravenous antibiotics for two days before discharge home on oral antibiotics. The patient returned to the ED three days later with worsening abdominal pain and peritoneal signs on physical examination. Results: Triphasic contrast-enhanced CT of the abdomen revealed a perforated gallbladder with inflammation and active hemorrhage into the gallbladder and adjacent peritoneal space. At laparotomy, the inflamed, ruptured gallbladder was found adherent to the hepatic flexure of colon with a large hemoperitoneum. Cholecystectomy was performed and pathologic evaluation was consistent with features of acute and chronic cholecystitis with perforation. The patient recovered fully following a brief course in the intensive care unit and was discharged home one week later. Conclusion: Complications of acute cholecystitis include hemorrhage and perforation. CT imaging serves as a valuable adjunct in accurate recognition of such complications, allowing for prompt, appropriate intervention.